Albumin domain mutants with enhanced Aβ binding capacity identified by phage display analysis for application in various peripheral Aβ elimination approaches of Alzheimer's disease treatment. Issue 4 (3rd December 2019) - Ishima, Yu; Mimono, Ai; Tuan Giam Chuang, Victor; Fukuda, Tetsuya; Kusumoto, Kohshi; Okuhira, Keiichiro; Suwa, Yoshiaki; Watanabe, Hiroshi; Ishida, Tatsuhiro; Morioka, Hiroshi; Maruyama, Toru; Otagiri, Masaki
Abstract: Deposition of amyloid protein, particularly Aβ1‐42, is a major contributor to the onset of Alzheimer's disease (AD). However, almost no deposition of Aβ in the peripheral tissues could be found. Human serum albumin (HSA), the most abundant protein in the blood, has been reported to inhibit amyloid formation through binding Aβ, which is believed to play an important role in the peripheral clearance of Aβ. We identified the Aβ binding site on HSA and developed HSA mutants with high binding capacities for Aβ using a phage display method. HSA fragment 187–385 (Domain II) was found to exhibit the highest binding capacity for Aβ compared with the other two HSA fragments. To elucidate the sequence that forms the binding site for Aβ on Domain II, a random screening of Domain II display phage biopanning was constructed. A number of mutants with higher Aβ binding capacities than the wild type were identified. These mutants exhibited stronger scavenging abilities than the wild type, as revealed via in vitro equilibrium dialysis of Aβ experiments. These findings provide useful basic data for developing a safer alternative therapy than Aβ vaccines and for application in plasma exchange as well as extracorporeal dialysis.